Macrofossil Characteristics and Bathymetric Environment of Sumber Makmur Village, Muara Sahung, Kaur, Bengkulu - Maulia, Dita; Idarwati, Idarwati (Journal of Earth and Marine Technology (JEMT), 2023)
The research location is administratively located in Sumber Makmur Village, Muara Sahung District, Kaur Regency, Bengkulu Province. In the study area, outcrops that had fossils were found, which were shown by the presence of carbonate rock lithology. The study was conducted to determine the deposition environment in the research area. The method used is a previous literature study that aims to determine the physical geological conditions and regional stratigraphy of the research area. Furthermore, field observations and laboratory analysis were conducted in the form of paleontological analysis to determine the characteristics and types of fossils found in the study area. Paleontological research was conducted on two formations, namely the Lemau Formation and the Simpangaur Formation. In the Lemau Formation, several species of benthic foraminifera were found, namely Cibicides praecinestus, Elphidium macelium, Marginopora vertebralis, Elphidium articulatum, and Planorbulina mediterranensis. Then, in the Simpangaur Formation, several species of benthic foraminifera were found, namely Streblus beccari, Bolivina schwageriana, Anomalinella rostrate, Cibides praecinestus, Cibides margaritiferus, Lagena sulcata, Quinqueloculina bradyana, and Lenticulina calcar. In addition, macrofossils were found in marine life with phylum mollusks such as Lunatia elevatum, Murex vanuxemi, Turritella terebra, Conus sauridens, and Plocostoma neumayeri. Based on these data, it can be interpreted that the depositional environment in the study area is in the Transition-Edge Neritic marine environment.